TorakochirurgiaMeasurement of activity of glutathione peroxidase (GPX) and superoxide dismutase (SOD) in diagnosis of diffuse lung diseases - Santorek-Strumiłło, Edyta J.; Piskorz, Łukasz; Wcisło, Szymon; Brocki, Marian; Jabłoński, Sławomir; Kordiak, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: The most common causes of diffuse lung diseases are: advanced forms of cancer and cancer metastasis – both connected with oxidative stress. The oxidative stress leads to the creation of oxygen free radicals which can damage the structure of nucleic acids, in consequence rupturing chromosomes. A consequence of this process is mutation and initiation of the neoplastic process. Aim: The aim of the work was to define the dependence of GPX and SOD activity in blood and lung tissues for aetiology of diffuse lung diseases. Material and Methods: Research material involved a group of 40 persons with diffuse lung diseases (lung cancer, sarcoidosis) and 40 persons constituting a control group. The investigated group consisted of patients with diffuse lung diseases, which was diagnosed in different hospitals based on examination of material collected by traditional, small invasive method; however, aetiopathogenesis had not been discovered. Activity of GPX and SOD was measured in blood and lung tissues. Research material was 5.4 ml of venous blood collected once from veins of the cubital hole region and also a fragment of the lung tissues gained during videothoracoscopy. Results: The research showed statistically significantly lower values of GPX in blood and lung tissues in the investigated group compared to the control group and also inverse dependence in the activity of SOD. Conclusions: Measurement of activity of glutathione peroxidase and superoxide dismutase in the blood is a good, minimally invasive, additional laboratory test, helpful in the qualification of the aetiology of diffuse lung diseases.